Antioxidant properties of catechins: Comparison with other antioxidants - Grzesik, Michalina; Naparło, Katarzyna; Bartosz, Grzegorz; Sadowska-Bartosz, Izabela (Food chemistry, 2018)
•Antioxidant properties of catechins and other antioxidants were compared.•Catechins were most reactive in ABTS and FRAP assays.•Flavonoids effectively protected against SIN-1, AAPH and NaOCl reactions.•Catechins best protected against AAPH- and NaOCl-induced hemolysis.•Catechins most effectively inhibited intracellular H2DCF oxidation by AAPH. Antioxidant properties of five catechins and five other flavonoids were compared with several other natural and synthetic compounds and related to glutathione and ascorbate as key endogenous antioxidants in several in vitro tests and assays involving erythrocytes. Catechins showed the highest ABTS-scavenging capacity, the highest stoichiometry of Fe3+ reduction in the FRAP assay and belonged to the most efficient compounds in protection against SIN-1 induced oxidation of dihydrorhodamine 123, AAPH-induced fluorescein bleaching and hypochlorite-induced fluorescein bleaching. Glutathione and ascorbate were less effective. (+)-catechin and (−)-epicatechin were the most effective compounds in protection against AAPH-induced erythrocyte hemolysis while (−)-epicatechin gallate, (−)-epigallocatechin gallate and (−)-epigallocatechin protected at lowest concentrations against hypochlorite-induced hemolysis. Catechins [(−)-epigallocatechin gallate and (−)-epicatechin gallate)] were most efficient in the inhibition of AAPH-induced oxidation of 2′7′-dichlorodihydroflurescein contained inside erythrocytes. Excellent antioxidant properties of catechins and other flavonoids make them ideal candidates for nanoformulations to be used in antioxidant therapy.